Saunders computerized review for NCLEX-RN - Silvestri, Linda Anne (Philadelphia : W. B. Saunders, 2002)
Study guide for the NCLEX-RN that measures the user's readiness to take the test.Generates study mode, quiz mode, or exam mode in which 100-question practice exams are selected from a pool of 2000 questions to emulate the content and format of the NCLEX-RN test plan and provides answers, rationales, test taking strategy, reference source, and results
System requirements : Windows ; 95, 98, 2000, ME, or NT Pentium or faster processor, at least 32 MB RAM recommended, 10 MB free hard disk space, 2X or faster CD-ROM drive, 640 x 480 monitor or larger, true color display recommended
System requirements : Macintosh ; OS 7.6.1 or greater, at least 32 MB RAM recommended, 10 MB free hard disk space, 2X or faster CD-ROM drive, 640 x 480 monitor or larger, millions of colors display recommended
Keywords: Nursing Care; Nursing process; Examination Questions